2019
DOI: 10.1093/inthealth/ihz025
|View full text |Cite
|
Sign up to set email alerts
|

On the verge of a chronic disease epidemic: comprehensive policies and actions are needed in Indonesia

Abstract: In the midst of tackling the persistent burden of maternal mortality and infectious diseases, Indonesia is facing an increasing burden of non-communicable diseases (NCDs). Although there are increasing national efforts in NCD prevention and control, the worsening trend of NCD risk factors and morbidity is alarming. We provided assessment and discussion on the policies and actions needed in the country including comprehensive efforts to reduce tobacco use and unhealthy diet, the need to reorient the health syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Secondly, comprehensive policies to promote a healthy diet is needed to help reduce obesity, hypertension, and diabetes in urban, wealthier, and most educated districts. Strategies may include taxes on unhealthy foods, subsidies on healthy foods, and regulations on salt, sugar and trans-fat [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, comprehensive policies to promote a healthy diet is needed to help reduce obesity, hypertension, and diabetes in urban, wealthier, and most educated districts. Strategies may include taxes on unhealthy foods, subsidies on healthy foods, and regulations on salt, sugar and trans-fat [4].…”
Section: Discussionmentioning
confidence: 99%
“…Like many low and middle-income countries (LMICs), the burden of CVDs and risk factors is high and increasing in Indonesia, a lower-middle-income country [4]. The Global Burden of Disease study shows that stroke and ischemic heart disease are the top causes of deaths and disability in 2017 [5].…”
Section: Introductionmentioning
confidence: 99%
“…For those living with a chronic disease, it has a significant impact on functioning, quality of life, and well-being, while for society, it has implications for productivity and healthcare costs. Although prevention and health promotion initiatives are needed to curb the rising rates of chronic disease, there is also a need to improve healthcare and services in order to better support those already affected by an illness [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Indonesian Global Burden of Disease study showed ischemic heart disease and stroke as the top two leading causes of death and disability in 2016 [3]. Despite all this, the national tobacco control programs are very limited in Indonesia, partly due to not yet ratifying the Framework Convention on Tobacco Control (FCTC) [4][5][6].…”
Section: Introductionmentioning
confidence: 99%